2022
DOI: 10.3389/fpls.2022.1001158
|View full text |Cite
|
Sign up to set email alerts
|

Radiation environment in exploration-class space missions and plants’ responses relevant for cultivation in Bioregenerative Life Support Systems

Abstract: For deep space exploration, radiation effects on astronauts, and on items fundamental for life support systems, must be kept under a pre-agreed threshold to avoid detrimental outcomes. Therefore, it is fundamental to achieve a deep knowledge on the radiation spatial and temporal variability in the different mission scenarios as well as on the responses of different organisms to space-relevant radiation. In this paper, we first consider the radiation issue for space exploration from a physics point of view by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…This stage represents a very delicate phase in the plant life cycle because after the break of dormancy, the plant is characterized by active meristems and morphogenesis, particularly vulnerable to abiotic stress, which may weaken the seedling establishment [59]. In space, the presence of ionizing radiation [29,30,44] may influence early morphogenesis in plants [45][46][47]. Previous research has demonstrated that low doses of X-rays may generally induce positive effect on the viability, germination, and growth of the seeds, while high doses may reduce or hamper these delicate phases [35,60,61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This stage represents a very delicate phase in the plant life cycle because after the break of dormancy, the plant is characterized by active meristems and morphogenesis, particularly vulnerable to abiotic stress, which may weaken the seedling establishment [59]. In space, the presence of ionizing radiation [29,30,44] may influence early morphogenesis in plants [45][46][47]. Previous research has demonstrated that low doses of X-rays may generally induce positive effect on the viability, germination, and growth of the seeds, while high doses may reduce or hamper these delicate phases [35,60,61].…”
Section: Discussionmentioning
confidence: 99%
“…In the experiments of radiobiology performed on Earth, considering the reduced possibility to recreate all the radiation spectrum and their dose intensity, particle accelerators are used. In these facilities, dose rates of many orders of magnitude higher than those in space are normally used to reduce the duration of the trials and to estimate the possible effects that would occur with lower doses over a longer period of time [44].…”
Section: Introductionmentioning
confidence: 99%
“…Plants are the primary food producers for humans on Earth and have the potential to accomplish the same task in space. Furthermore, by consuming carbon dioxide and producing oxygen through photosynthesis, purifying water from the collection of transpired water, and having a role in waste recycling, they are well-suited for the regeneration of resources 15 . Although regeneration of resources in short-term missions would be a “nice-to-have” requirement, it becomes a “must-have” in long-term missions where resupply from Earth would not be feasible and where initial launch mass to carry all consumables would be prohibitive.…”
Section: The Higher Plant Compartmentmentioning
confidence: 99%
“…different species/cultivars, target organs/tissues). Recently, more attention has been dedicated to the effect of ionizing radiation (IR) so far as it represents a clear challenge for exploratory-class missions 14 . Altered gravity and exposure to IR can induce changes in gene expression, cell proliferation and differentiation, signalling and physiological processes (see precise data and references in the following paragraphs).…”
Section: What Is Already Known About the Effects Of Microgravity And ...mentioning
confidence: 99%
“…Outside Low Earth Orbit, IR is variable in space and time and can severely constrain organisms’ growth 3 , 14 . IR can cause direct damage to the structures encountered, but also indirect due to the generation of reactive oxygen species (ROS) 64 , 65 .…”
Section: What Is Already Known About the Effects Of Microgravity And ...mentioning
confidence: 99%